SEM-PLS : Determinan Minat Beli Produk UMKM (Studi Empiris Produk Desa Wisata Samosir) - Toto Budiharto (CERED Indonesia Institute, 2021)
This study uses the SEM-Partial Least Square (PLS) approach. PLS is a component-based or variant-based Structural Equation Modeling (SEM) equation model. Hypothesis testing is carried out using the Bootstrap resampling method with a minimum number of bootstrap as many as 217 and the number of cases must be the same as the number of observations in the original sample. The results of this study prove that attitude has a positive and significant effect on buying interest which proves the hypothesis is accepted. This means that the better the attitude shown to Samosir products, the more buying interest in Samosir tourism visitors will be. The test results provide empirical evidence that the price has a positive and insignificant effect on buying interest which proves the hypothesis is rejected. Of course, this finding shows how price cannot affect buying interest so that SMEs are expected to be able to evaluate the price so that it remains in accordance with the buying interest of tourist visitors in buying. The test results provide empirical evidence that trust has a positive and significant effect on buying interest which proves the hypothesis is accepted.